Case report: Osteosarcomatous differentiation in the lung metastasis of a malignant phyllodes tumor - Liu, Ruijing; Xue, Jingli; Liu, Wen; Jiang, Beibei; Shi, Fuyun; Wang, Zhenzheng; Li, Peifeng (Frontiers in Medicine, 2023)
Malignant phyllodes tumor is a rare breast tumor, with distant metastases and heterologous differentiation in a few cases. We report a case of malignant phyllodes tumor with liposarcomatous differentiation in the primary tumor and osteosarcomatous differentiation in the lung metastatic tumor. A middle-aged female presented with a well-defined mass in the upper lobe of the right lung measuring 5.0 × 5.0 × 3.0 cm. The patient had a history of malignant phyllodes tumor in the breast. The patient underwent a right superior lobectomy. Histologically, the primary tumor was a typical malignant phyllodes tumor with pleomorphic liposarcomatous differentiation, while the lung metastasis showed osteosarcomatous differentiation without original biphasic features. The phyllodes tumor and heterologous components showed CD10 and p53 expression, and were negative for ER, PR, and CD34. Exome sequencing revealed TP53, TERT, EGFR, RARA, RB1, and GNAS mutations in all three components. Although the lung metastasis were morphologically different from the primary breast tumor, their common origin was demonstrated through immunohistochemical and molecular characterization. Cancer stem cells give rise to tumor heterogeneous cells, and heterologous components in malignant phyllodes tumors may indicate unfavorable prognosis and a greater risk of early recurrence and metastasis.